Congenital Segmental Lymphedema in Tuberous Sclerosis Complex With Associated Subependymal Giant Cell Astrocytomas Treated with Mammalian Target of Rapamycin Inhibitors. (September 2014) - Prato, Giulia; Mancardi, Maria Margherita; Baglietto, Maria Giuseppina; Janis, Sara; Vercellino, Nadia; Rossi, Andrea; Consales, Alessandro; Raso, Alessandro; Garrè, Maria Luisa
Tuberous sclerosis complex is a genetic, multisystemic disorder characterized by circumscribed benign lesions (hamartomas) in several organs, including brain. This is the result of defects in the TSC1 and/or TSC2 tumor suppressor genes, encoding the hamartin-tuberin complex that inhibits the mammalian target of rapamycin pathway. Specific inhibitors of this pathway have been shown to reduce the volume of subependymal giant cell astrocytomas associated with tuberous sclerosis. Congenital lymphedema is rarely seen in association with tuberous sclerosis, with only a few reported cases. Although this association can be coincidental, the dysgenetic lymphatic system can represent a hamartia as a consequence of gene mutation. We describe a child with congenital lymphedema in tuberous sclerosis and associated subependymal giant cell astrocytoma who experienced lymphangitis under treatment with mammalian target of rapamycin inhibitors. Because our patient did not show worsening of lymphedema, congenital lymphedema does not seem to be a contraindication for this therapy.